2004
DOI: 10.1167/iovs.04-0598
|View full text |Cite
|
Sign up to set email alerts
|

FAS-Mediated Apoptosis and Its Relation to Intrinsic Pathway Activation in an Experimental Model of Retinal Detachment

Abstract: The FAS-mediated apoptosis pathway becomes activated and transcriptionally upregulated after retinal detachment. The peak of FAS activation precedes that of the intrinsic pathway, and inhibition of FAS activation can decrease caspase-9 activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
100
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(107 citation statements)
references
References 15 publications
7
100
0
Order By: Relevance
“…S7 C and D), suggesting that TNF-α may contribute to the induction of apoptosis and programmed necrosis. In addition to TNF-α, Fas-L/Fas pathway is known to be activated and mediate photoreceptor death after retinal detachment (19,42), and may cooperate with TNF-α to activate RIP kinases and promote programmed necrosis in addition to apoptosis. Thus, RIP kinases act as common intermediaries for various upstream death signals and their blockade in addition to caspases is likely necessary for effective neuroprotection (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S7 C and D), suggesting that TNF-α may contribute to the induction of apoptosis and programmed necrosis. In addition to TNF-α, Fas-L/Fas pathway is known to be activated and mediate photoreceptor death after retinal detachment (19,42), and may cooperate with TNF-α to activate RIP kinases and promote programmed necrosis in addition to apoptosis. Thus, RIP kinases act as common intermediaries for various upstream death signals and their blockade in addition to caspases is likely necessary for effective neuroprotection (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…During death domain receptor-induced apoptosis, RIP1 is cleaved and inactivated by caspase-8, the process of which is prevented by caspase inhibition (13). It has been unclear how RIP1 kinase mediates programmed necrosis, but recent studies revealed that the expression of RIP3 and the RIP1-RIP3 binding through the RIP homotypic interaction motif is a prerequisite for RIP1 kinase activation, leading to reactive oxygen species (ROS) production and necrotic cell death (14-16).In a rodent model of retinal detachment, we have shown that TNF-α expression levels increase substantially (17) and that caspases are activated after retinal detachment (18,19). However, caspase inhibition by Z-VAD fails to prevent the retinal detachment-induced photoreceptor death (20).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier studies mainly focused on the mitochondrion-mediated pathway; the existence of mitochondrion-mediated pathway has been confirmed in the apoptosis of photoreceptors whereby the inhibition of key factors in above pathway prevented the photoreceptors from apoptosis. [8][9][10] However, the inhibitors can only partly rescue photoreceptors, suggesting the existence of other pathways for the apoptosis process after RD.…”
Section: Introductionmentioning
confidence: 99%
“…31,32 This study showed that exogenous EPO after RD significantly reduced the number of TUNEL-positive cells, indicating that EPO partially inhibited apoptosis. Caspase-3 is the final executor of apoptosis and is also involved in photoreceptor cell apoptosis after RD.…”
Section: Eyementioning
confidence: 78%